Determinants of Commercial Banks’ Profitability in Malaysia - Trofimov, Ivan D.; Nazaria, Md.Aris; Kho, Jovena Ying Ying (MPRA Paper, 2018)
This study aims to examine the relationship between non-performing loans (NPLs) and commercial banks' performance in Malaysia, alongside other factors. It considers the effect of NPLs, cost efficiency and bank size on commercial banks' profitability by using panel data regression (Pooled OLS model), covering the period of 2010-2015. The findings of the study show that NPLs and cost efficiency have a significant negative relationship with commercial banks' performances in Malaysia. On the other hand, bank size is found to have a significant positive relation with commercial banks' performances in Malaysia. Several policy and strategic implications are outlined: the continuing need to manage credit risk, reduction of non-core lending activities, improvement of systems transparency, cost control, and more lenient competition and anti-trust policies. Keywords: profitability, non-performing loans, banks